The Challenges of New Students of Universitas Negeri Makassar (UNM) in Essay Writing - Sakkir, Geminastiti; Dollah, Syarifuddin; Sakkir, Rini Isnaeni (ARRUS Journal of Social Sciences and Humanities, 2024)
This research investigates the challenges faced by new students of the English Language Education Study Program at Universitas Negeri Makassar (UNM) in writing essays. Writing is a complex skill that involves the organization of ideas, proper use of grammar, and clarity of expression. New students often struggle with various aspects of essay writing, which can hinder their academic progress. The study employs a qualitative research approach, focusing on 142 students from the second semester of the 2023/2024 academic year. Data was collected through interviews and analyzed descriptively. The findings reveal several key challenges that students encounter when writing essays. These include difficulties with English grammar, low vocabulary, challenges organizing ideas, and issues expressing thoughts clearly. Additionally, students face non-technical obstacles such as a lack of confidence, poor time management, and the physical strain of writing. The study highlights that the essay writing process is multifaceted, requiring not only technical skills but also critical thinking and self-management abilities. Understanding these challenges provides valuable insights for educators in designing more effective teaching strategies. By addressing both the technical and psychological barriers to writing, lecturers can help students improve their essay-writing skills and better prepare them for higher academic demands. The research emphasizes the importance of a comprehensive approach to teaching writing, one that considers the diverse challenges faced by students and aims to enhance their overall academic performance.